2004
DOI: 10.1103/physrevb.69.125115
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculation of the electronic structure ofBa0.5Sr0.5TiO

Abstract: First-principles quantum-mechanical techniques, based on density functional theory ͑B3LYP level͒ were employed to study the electronic structure of ordered and deformed asymmetric models for Ba 0.5 Sr 0.5 TiO 3 . Electronic properties are analyzed and the relevance of the present theoretical and experimental results on the photoluminescence behavior is discussed. The presence of localized electronic levels in the band gap, due to the symmetry break, would be responsible for the visible photoluminescence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 34 publications
5
51
0
1
Order By: Relevance
“…Theoretical results have shown that the symmetry break process (an effect of order-disorder) in the structure of various semiconductors is a condition necessary for the existence of intermediary energy levels within the forbidden bandgap. 45 As shown in Figs. 5(a)-5(f), the evolution of the PL spectra was obviously different.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Theoretical results have shown that the symmetry break process (an effect of order-disorder) in the structure of various semiconductors is a condition necessary for the existence of intermediary energy levels within the forbidden bandgap. 45 As shown in Figs. 5(a)-5(f), the evolution of the PL spectra was obviously different.…”
Section: Resultsmentioning
confidence: 79%
“…In the case of capped ZnS, the recombination of electrons and holes gives rise to a strong green light emission and in the case of uncapped ZnS, to blue light emission. In our model, the wide-band model, 45 the most important events occur before excitation, i.e., before the photon arrives. The deep and shallow defects generated by the complex clusters give rise to localized states in the bandgap and inhomogeneous charge distribution in the cell, allowing electrons to become trapped.…”
Section: -mentioning
confidence: 99%
“…14,15 The PL at room temperature occurs due to structural disorder of the system. Therefore, if the system is totally disordered, then the PL does not exist; moreover, a totally ordered system does not exhibit PL.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if the system is totally disordered, then the PL does not exist; moreover, a totally ordered system does not exhibit PL. 12,14 The analysis of structural disorder in these PZT powders helps to understand the origin of PL emission. Figure 3 presents X-ray diffractograms of the PZT powders annealed at 300°C for 4, 8 and 16 h and annealed at 700°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation